ANALISIS IMPLEMENTASI STANDAR AKUNTANSI KEUANGAN ENTITAS PRIVAT (EP) PADA PENYUSUNAN LAPORAN KEUANGAN PT AMANAH UMAT SUKSES KOTA JAMBI - Ratmi Indah Eka Safitri; Elyanti Rosmanidar; Muthmainnah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of SAK EP in the preparation of financial statements at PT Amanah Umat Sukses, Jambi City, using a descriptive qualitative method with a case study approach. The results indicate that administra- tively the company has successfully compiled all five components of the financial statements completely, but substantively the reporting practices are not yet fully in compliance with SAK EP. Significant obstacles were found in the presentation and measurement aspects such as the pooling of expense accounts and the omission of systematic fixed asset depreciation which have the potential to cause net income to be reported as overly high (overstated). Based on the compliance analysis, the recognition and measurement pillars achieved a conformity level of 80%, while the presentation pillar fell into the